2012
DOI: 10.1186/2251-7235-6-30
|View full text |Cite
|
Sign up to set email alerts
|

*Investigation on the formation of titanium nitride thin films on 304 type stainless steel using plasma focus device

Abstract: In the present paper, we see the effect of shapes of perturbing pulses on the evolution of electromagnetic solitons in a plasma having nonrelativistic ions and electrons. For this, we make use of IMEX scheme in our simulations, which is an invariant scheme for the two-fluid plasma flow equations. In particular, the impact of ion-to-electron mass ratio, electronto-ion temperature ratio and the width of perturbing pulse is examined on the phase velocity, peak amplitude and width of the solitons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Regarding the as-deposited TiN thin films on quartz, only the (200) plane was observed, in accordance with previous reports. , After irradiation, the diffraction patterns of the TiN thin films on quartz showed a characteristic peak at 44°, identified as the (200) plane, but with lower intensity than the as-deposited TiN thin films on quartz (Figure ). Interestingly, the irradiated TiN thin films on quartz reveal a peak with a high intensity at 40°, identified as the (111) plane.…”
Section: Resultssupporting
confidence: 90%
“…Regarding the as-deposited TiN thin films on quartz, only the (200) plane was observed, in accordance with previous reports. , After irradiation, the diffraction patterns of the TiN thin films on quartz showed a characteristic peak at 44°, identified as the (200) plane, but with lower intensity than the as-deposited TiN thin films on quartz (Figure ). Interestingly, the irradiated TiN thin films on quartz reveal a peak with a high intensity at 40°, identified as the (111) plane.…”
Section: Resultssupporting
confidence: 90%
“…TiN has metal-like characteristics having low resistivity, high mechanical hardness, as well as good wear resistance, and high corrosion resistance; 20,21 these properties have many applications, such as protective coatings on mechanical parts and anti-reflective coatings. [22][23][24] TiN has many applications in microelectronics, such as diffusion barrier layer, gate materials, adhesive layer, and Schottky barrier contacts. 22,25,26 Based on the properties of TiN, such as its CMOS compatibility, biocompatibility, durability, and robustness for a wide pH range and thus, it is suitable for chemical/ biochemical sensing and in-vivo monitoring applications.…”
mentioning
confidence: 99%
“…This confirms that more uniform and smooth films are deposited at lower ion energy flux (10 • angular position) as revealed in SEM results. Fani and Savaloni synthesized the TiN film using DPF and found that the roughness decreases with increasing angular position (15). The AFM micrographs of the films deposited at 10 • angular position are shown in Figure 8.…”
Section: Resultsmentioning
confidence: 97%
“…Masugata et al proposed that the ion beam pulse emitted from DPF can be used for surface treatment on semiconductors (14). The DPF device has been used earlier for the synthesis of different films such as TiN, TiN/a-Si 3 N 4 , and (Ti,Al)N/a-Si 3 N 4 (11,(15)(16)(17)(18)(19)(20). However, it is significant to mention that we have used DPF first time for the synthesis of the TiN/Ni 3 N/a-Si 3 N 4 thin film.…”
Section: Introductionmentioning
confidence: 93%